Alliance Management Capability: An Investigation of the Construct and Its Measurement - Schilke, Oliver; Goerzen, Anthony (Journal of Management, 2010)
This research conceptualizes and operationalizes alliance management capability. The authors develop alliance management capability as a second-order construct to capture the degree to which organizations possess relevant management routines that enable them to effectively manage their portfolio of strategic alliances. In addition to identifying and measuring specific organizational routines as critical dimensions of alliance management capability, the authors advance knowledge on the performance effects of dedicated alliance structures and alliance experience based on survey data from 204 firms. Their primary contribution is a theoretically sound alliance management capability measure that is reflected by five underlying routines: interorganizational coordination, alliance portfolio coordination, interorganizational learning, alliance proactiveness, and alliance transformation. One of the key findings is that alliance management capability has a positive impact on alliance portfolio performance and mediates the performance effects of dedicated alliance structures and alliance experience.